Analysis Of Students' Mathematical Reasoning Abilities In Solving Trigonometry Problems In Grade X - Revol A. Sibarani; Agusmanto Hutauruk; Rani Farida Sinaga (STABN RADEN WIJAYA WONOGIRI, 2021)
This study aims to analyze the mathematical reasoning ability of tenth-grade students at SMA Free Methodist Medan in solving trigonometry problems. The research employed a sequential mixed-methods design by combining quantitative and qualitative approaches, with a saturated sampling technique involving all tenth-grade students. The research instrument consisted of essay tests covering four indicators of mathematical reasoning ability: proposing conjectures, performing mathematical manipulations, providing proof and justification of solutions, and drawing conclusions. The results revealed that students' mathematical reasoning ability was categorized as high. The most mastered indicator was proposing conjectures, while the least mastered was drawing conclusions. Overall, the distribution of students' abilities falls into the categories of very high, high, medium, low, and very low. These findings indicate that students' mathematical reasoning ability still needs improvement, particularly in providing evidence and justification as well as drawing valid conclusions.